Steel drum troupe highlights Raton Art Council's fundraiser (Raton, NM Raton Range, 1994)
Article is about the Steel Bandits to perform at the Art and Humanities Councils fundraiser.
Newspaper article
Master list item #: 47
File location is in the Raton file Cabinet
Keywords: Steel Bandits -- Music Troupe; Performance Review; Art and Humanities Council; Fundraising